Surveillance Study (2000 to 2001) of G- and P-Type Human Rotaviruses Circulating in South Korea - Min, Bok Soon (American Society for Microbiology, 2004)
Human rotavirus VP4 and VP7 gene sequences were amplified by reverse transcription-PCR from 53% (322 of 607) of fecal specimens collected from children with severe diarrhea who visited hospitals in six urban areas of South Korea in 2000 and 2001. G2 was the most frequently found G type (constituted 50.6%), followed by G1 (30.1%) and G4 (13.0%). Although the P types of high incidence were P[4] (53.1%) and P[8] (21.4%), a significant incidence of P[6] (20.2%) was also noticeable. The commonest G- and P-type combination found in this study was G2P[4], rather than G1P[8], the most prevalent type known worldwide.